Indirect calculation of mechanical and propelling efficiency during freestyle swimming - Cappaert, J. M.; Franciosi, P. Q.; Langhans, G. W.; Troup, J.P. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
This study aims at perfecting and evaluating experimental equipment which responds to the bio-feedback principle. The equipment is composed of two systems which can be used separately or simultaneously by the swimmer. The first is composed of stroke information paddles allowing the swimmer to be informed about the hydrodynamic pressure in his hand during the stroke, whilst the second is composed of a swimmer's speed variation measuring device which transforms the data into auditory information. In order to evaluate the use of the bio-feedback in crawl, a study was performed using four groups of swimmers. Three groups were equipped with the informative equipment and the fourth was the control group (neutral equipment). The results obtained after 5 and 15 days demonstrated that a swimmer informed on the speed variations parameter first and then simultaneously receiving the pressure and speed information, can significantly improve swimming performance.